2007
DOI: 10.1029/2006jg000238
|View full text |Cite
|
Sign up to set email alerts
|

Reactive transport of trace elements and isotopes in the Eutaw coastal plain aquifer, Alabama

Abstract: [1] We integrate groundwater geochemistry, mineralogy, and numerical modeling techniques to study the reactive transport of heavy metals and isotopes in the Eutaw coastal plain aquifer, Alabama. Geochemical data show that the elevated concentrations of Fe, Mn, and Sr can be correlated with high pH and alkalinity. These geochemical correlations suggest that that elevated metal concentrations may be derived from bacterial iron and manganese reduction. Geochemical modeling of bacterial Fe(III) and Mn(IV) reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 49 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…The trace amount of Mn oxides, one of the important oxidants in aquifers (Gao, Guo, et al., 2020; Owings et al., 2019), favors groundwater As remaining as As(III) species, which is less adsorbed and thus is more mobile than As(V) (Dixit & Hering, 2003). On the other hand, the low abundant Mn oxides facilitate reduction of As‐bearing Fe(III) oxides based on the classical redox sequence (Lee et al., 2007), which thus leads to As release into groundwater. Similar conditions have also been observed in a Pleistocene aquifer from Cambodia with limited total Mn contents in sediments (around 0.47 mmol/kg), where high‐As groundwater (1.13–4.61 μmol/L) was observed (Gillispie et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The trace amount of Mn oxides, one of the important oxidants in aquifers (Gao, Guo, et al., 2020; Owings et al., 2019), favors groundwater As remaining as As(III) species, which is less adsorbed and thus is more mobile than As(V) (Dixit & Hering, 2003). On the other hand, the low abundant Mn oxides facilitate reduction of As‐bearing Fe(III) oxides based on the classical redox sequence (Lee et al., 2007), which thus leads to As release into groundwater. Similar conditions have also been observed in a Pleistocene aquifer from Cambodia with limited total Mn contents in sediments (around 0.47 mmol/kg), where high‐As groundwater (1.13–4.61 μmol/L) was observed (Gillispie et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Huntite, could be particularly difficult to detect on Mars (especially if present in low amounts) since it is metastable at surface temperature (Garrels et al, 1960;Kinsman, 1967) and it is replaced with time by magnesite (Kinsman, 1967;Spotl and Burns, 1994;Marini, 2007), a more stable Mg-carbonate that is present on the Martian ground together with siderite, calcite, rhodochrosite and other Mg-and Fe-bearing alteration minerals (Ehlmann et al, 2008;Niles et al, 2013;Goudge et al, 2015). Finally, alteration phases predicted to form in the biotic system (siderite, rhodochrosite, quartz, pyrite, hydroxyapatite) are all minerals that naturally can precipitate in near-neutral pH aqueous environments at ambient temperature following the action of microbes (Lee et al, 2007;Ehrlich and Newman, 2009;Sun et al, 2014;Duverger et al, 2020).…”
Section: Alteration Minerals and Life Detection On Marsmentioning
confidence: 99%
“…In some studies, qualitative analysis of the aquifer sediments is performed to corroborate inferences from groundwater analyses and modelling (e.g. Lee et al 2007). Quantitative studies of sediment reactivity are found mainly in connection with local contaminant plumes, with some recent studies addressing the problem of As mobilisation in drinking water aquifers (Swartz et al 2004;Shamsudduha et al 2008).…”
mentioning
confidence: 99%